The international law of belligerent occupation / Yoram Dinstein. - Dinstein, Yoram (Cambridge University Press, 2009)
The customary law of belligerent occupation goes back to the Hague and Geneva Conventions. Recent instances of such occupation include Iraq, the former Yugoslavia, the Congo and Eritrea. But the paradigmatic illustration is the Israeli occupation, lasting for over 40 years. There is now case law of the International Court of Justice and other judicial bodies, both international and domestic. There are Security Council resolutions and a vast literature. Still, numerous controversial points remain. How is belligerent occupation defined? How is it started and when is it terminated? What is the interaction with human rights law? Who is protected under belligerent occupation, and what is the scope of the protection? Conversely, what measures can an occupying power lawfully resort to when encountering forcible resistance from inhabitants of the occupied territory? This book examines the legislative, judicial and executive rights of the occupying power and its obligations to the civilian population.